Effect of Mangosteen Peel Extract on SGOT and SGPT in Rats Fed Reused Cooking Oil - Widyastuti, Esti; Maharani, Nani; Utomo, Astika Widy (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2018)
Background: Free radicals that enter the body due to consumption of reused cooking oil can cause liver cell damage. Mangosteen peel extract (Garcinia mangostana L) is known to contain mangostin as an ntioxidant. However, it is not known whether it can repair liver damage.Objective: To deter mine the ef fect of mangosteen peel extract on the levels of SGOT and SGPT of Wistar rats fed with reused cooking oil.the ef fect of mangosteen peel extract on the levels of SGOT and SGPT of Wistar rats fed with reused cooking oil.Methods: This study was a tr ue experimental study with post-test only controlled group design. Twenty four male Wistar rats were randomly divided into 4 groups randomly. The CN-G group was given the standard diet, the MJ-G group was given a standard diet and cooking oil, the MJM- 400 group was given standard diet, reused cooking oil, and mangosteen peel extract at a dose of 400 mg/KgBW, and the MJM-800 group was fed with a standard, reused cooking oil, and mangosteen peel extract at 800mg/KgBW. The treatment was car ried out for 28 days, and then continued with examination of reused cooking oil, and mangosteen peel extract at 800mg/KgBW. The treatment was car ried out for 28 days, and then continued with examination of SGOT and SGPT levels using the Inter national Federation of Clinical Chemistr y (IFCC) method without Pyridoxal Phosphate 37ÂºC.Results: Kr uskal Walis test showed that SGOT and SGPT levels showed no signif icant dif ferences between groups (p = 0.197 and 0.063, respectively).Conclusion: administration of mangosteen (Garcinia mangostana L) peel extract did not af fect SGOT levels, even tended to increase SGPT levels in ratsinduced by cooking oil.